Лаффасий ҳаёти ва ижоди - do’stova, surayyo (FILOLOGIYA UFQLARI JURNALI, 2022)
In rhis article is anylized Laffasiy’s life and his’v,orl<s on the based of scien- t iJic-cotnpctrut ft e v’ orks and manuscripts